Spatial variation of coastal wetland vulnerability to oil spill stress in the Bohai Sea - Wang, Yebao; Du, Peipei; Liu, Jiaqi; Chen, Chuntao (Frontiers in Marine Science, 2022)
Due to their position at the land–sea interface, coastal wetlands are extremely vulnerable to oil spills. However, few studies have focused on the vulnerability of coastal wetlands to oil spill hazards. In this study, we developed a spatial vulnerability approach and assessment based on the vulnerability scoping diagram in the Chinese Bohai Sea, where oil spill events are serious and frequent, and aimed to assess the spatial heterogeneity of the vulnerability of coastal wetlands under oil spill stress by integrating various indicators for exposure, sensitivity, and adaptive capacity into a composite index. This study normalized and aggregated data across sub-indices and combined related information with a geographic information system (GIS) model. The weighted results indicated that oil spill sources, as well as the natural environment in which the wetlands were located, dominated the degree of vulnerability of various coastal wetlands. The vulnerability assessment results suggest that there are obvious spatial variations among the different wetlands surrounding the Bohai Sea and each wetland had a different level of vulnerability, and highlights the need to enhance adaptive capacity to reduce vulnerability. This paper provides a quantitative assessment method for determining the spatial variation of coastal wetland vulnerability under oil spill stress, which can be used to better understand potential oil spill risks in coastal wetlands to support spill prevention and improve response readiness in the future.